2021
DOI: 10.3390/ijerph18062821
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and Motivations of Taiwanese People toward Advance Care Planning in Outpatient Clinics at a Community Hospital

Abstract: Advance care planning (ACP) provides access to complete advance decisions (ADs). Despite the legalization of ACP in Taiwan, it is underutilized in community settings. The objective of this study is to describe the service at a community hospital in Southern Taiwan. We retrospectively analyzed participants who were engaged in ACP consultations from January 2019 to January 2020. The characteristics, motivations, content, and satisfaction of participants are reported. Factors associated with refusing life-sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Similar to previous research results [ 35 , 36 ], participants who registered for organ donation were more likely to have ADs. This suggests an opportunity to increase awareness and receptivity towards organ donation by including a brief segment on this issue during ACP discussions [ 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to previous research results [ 35 , 36 ], participants who registered for organ donation were more likely to have ADs. This suggests an opportunity to increase awareness and receptivity towards organ donation by including a brief segment on this issue during ACP discussions [ 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…ACP encourages people to engage in discussions about future health choices and medical care. From the patients’ perspective, ACP prepares them for death and dying, allows them to exercise control, and relieves loved ones of the burden of decision making [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, two significant family-related factors contributing to the refusal of LST and ANH treatment were the reluctance of family members to assume responsibility and the rejection of HCA appointment. This mirrors the prevalent ACP issues in Asian culture, which primarily revolve around family-related concerns [ 6 , 15 ]. Sun et al reported instances in which ICU surrogates faced emotional interference from families with conflicting views on medical treatment, thereby influencing decision-making [ 27 ].…”
Section: Discussionmentioning
confidence: 81%
“…The preference of LST and ANH can be influenced by various factors, including culture, religion, tradition, value and beliefs, administrative guidelines, and the dynamics of the doctor– family–patient relationships [ 1 , 12 14 ]. Some studies have highlighted the challenges in providing ANH to the end-of-life patients [ 15 , 16 ]. Patients may require artificial nutrition for a variety of reasons, such as survival, feeling better, or maintaining appearances for the sake of their family [ 3 , 17 ].…”
Section: Discussionmentioning
confidence: 99%